Toleransi dalam masyarakat multikultural: Analisis literatur terhadap konsep, dinamika, dan implementasinya - rohmah, jazilatur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the concept, characteristics, dynamics, and implementation of tolerance in Indonesia’s multicultural society, as well as the role of national values in strengthening it. The method used is a literature review, examining various relevant scholarly sources. The results of the discussion indicate that tolerance is a fundamental value that serves as the foundation for maintaining social harmony amidst diversity. Indonesian multicultural society is characterized by high diversity, complex social interactions, and the potential for conflict arising from differences. In practice, tolerance is dynamic and influenced by various factors, such as globalization, social inequality, and the public’s level of understanding regarding diversity. Therefore, sustained efforts are needed to instill and develop the value of tolerance in social life. Tolerance can be implemented through education, social interaction, and inclusive government policies. Furthermore, the national values enshrined in Pancasila play a crucial role as a foundation for strengthening a tolerant attitude, as they embody the principles of humanity, unity, and social justice. Thus, tolerance is not merely a social value but also an integral part of the nation’s character that must be preserved and developed continuously.